Ventilation in the obese: physiological insights and management - Claudio Rabec; Jean-Paul Janssens; Patrick B. Murphy (European Respiratory Review)
Obesity can have profound adverse effects on the respiratory system, including an impact on pulmonary function, respiratory mechanics, respiratory muscle strength and endurance, gas exchange, control of breathing, and exercise capacity. Lung mechanics are modified by increased pleural pressure resulting from increased abdominal mass and subsequent peripheral airway occlusion and worsening of lung compliance due to reduced functional residual capacity without impairment of chest wall compliance. Arterial blood gases are frequently altered in these subjects and these abnormalities are directly proportional to body mass index. Mechanisms that may account for gas exchange abnormalities are multiple: ventilation/perfusion inequality (responsible for isolated hypoxaemia) and alveolar hypoventilation (responsible for so-called “obesity hypoventilation syndrome” (OHS)). Hypoventilation in obese patients results from a diversity of mechanisms, among which the two most frequently raised are mechanical limitation and blunted ventilatory drive. OHS is frequently underappreciated and diagnosis is frequently made during a first acute exacerbation. Obstructive sleep apnoea is a condition frequently associated with obesity and must be systematically screened for in this population because of its impact on morbidity and therapeutic management. Ventilatory management of these patients will depend on the patient's underlying situation, clinical presentation and physiology, including sleep study results; it may include continuous positive airway pressure or non-invasive ventilation. The goal of this narrative review is to provide a physiological-based overview of the impact of obesity on the respiratory system with a special focus on ventilatory management of patients with obesity-related respiratory disturbances.